Clinical-genetic analysis of selected genes involved in the development of the human skeleton in 128 Czech patients with suspected congenital skeletal abnormalities - Spurná, Z; Čapková, P; Punová, L; DuchoslavovÁ, J; Aleksijevic, D; Venháčová, P; Srovnal, J; Štellmachová, J; Curtisová, V; Bitnerová, Veronika; Petřková, J; Kolaříková, K; et al. (Gene, 2024)
BACKGROUND: Congenital skeletal abnormalities are a heterogeneous group of diseases most commonly associated with small or disproportionate growth, cranial and facial dysmorphisms, delayed bone maturation, etc. Nonetheless, no detailed genotype-phenotype correlation in patients with specific genetic variants is readily available. Ergo, this study focuses on the analysis of patient phenotypes with candidate variants in genes involved in bone growth as detected by molecular genetic analysis. METHODS: In this study we used molecular genetic methods to analyse the ACAN, COL2A1, FGFR3, IGFALS, IGF1, IGF1R, GHR, NPR2, STAT5B and SHOX genes in 128 Czech children with suspected congenital skeletal abnormalities. Pathogenic variants and variants of unclear clinical significance were identified and we compared their frequency in this study cohort to the European non-Finnish population. Furthermore, a prediction tool was utilised to determine their possible impact on the final protein. All clinical patient data was obtained during pre-test genetic counselling. RESULTS: Pathogenic variants were identified in the FGFR3, GHR, COL2A1 and SHOX genes in a total of six patients. Furthermore, we identified 23 variants with unclear clinical significance and high allelic frequency in this cohort of patients with skeletal abnormalities. Five of them have not yet been reported in the scientific literature. CONCLUSION: Congenital skeletal abnormalities may lead to a number of musculoskeletal, neurological, cardiovascular problems. Knowledge of specific pathogenic variants may help us in therapeutic procedures.
Keywords: frekvence genu; Česká republika; Growth Disorders; Child; Gene Frequency; lidé; Short Stature Homeobox Protein; genetické asociační studie; protein SHOX; dítě; Skeleton; Czech Republic; Genetic Association Studies; kostra; poruchy růstu; Humans